Leaf, Stem and Root Content of Proline in Atriplex Canescens and Suaeda Nigra - Limon, S. Moreno; Luna, R. Gonzalez; Aguirre, R. Garza; Pournavab, R. Foroughbakhch (International Journal of Bio-resource and Stress Management, 2014)
Although the list of factors that can affect the environment can be even more extensive, it is considered that an increase of salts in the soil represents a significant threat to the survival of plants, and consequently its impact on food levels, thereby decreasing the production and harvesting capacity in agricultural soils, causing large losses, both economic for the productive sector, such as biological considering the growing areas. For these reasons and in order to contribute to understanding the mechanisms of plant adaptation to salt stress conditions, in this investigation was determined by spectrophotometry the proline content in leaves, stems and roots of Suaeda nigra and Atriplex canescens, species of the family Chenopodiaceae, drawn by different methods. The average values of this amino acid content for both species, regardless of location, ranged from 25.614 to 2.457 μmol mg-1 for S. nigra and A. canescens, respectively. In S. nigra, the highest concentration of proline was 36.724 μmol mg-1 at the root, while in A. canescens the highest concentration was in the leaf with 3.951 μmol mg-1. Extraction methods did not influence the proline content of S. nigra, while in A. canescens, when the extract was obtained by the macerated plus sonicated with prior dilution method, the results were statistically higher than those obtained when the sample was drawn only by the sonication and subsequent dilution method. The proline content in both species is contrasting, however, these results showed a different trend in the compartmentalization, as in S. nigra, proline accumulates in the root, while in A. canescens, it does in the leaf.